LEVELS OF INDICATOR POLYCHLORINATED BIPHENYLS IN HUMAN MILK FROM VARNA REGION, BULGARIA - Temenuga Trifonova; Stanislava Katelieva Georgieva; Zlatina Peteva; Darina Hristova (Peytchinski Publishing, 2022)
Human milk is an appropriate tool for the assessment of the body burden of humans with lipophilic persistent organic pollutants such as polychlorinated biphenyls (PCBs). Purpose: The aims of the study were to determine the levels of polychlorinated biphenyls in the breast milk of women living in Varna, Bulgaria and to evaluate the association with demographic characteristics. Material and methods: Breast milk samples were collected in 2019 - 2020 from 28 healthy primiparae mothers. The six indicator PCB congeners were determined in individual mother's milk samples by capillary gas chromatography system with mass spectrometry detection (GC-MS). Results: The predominant PCB congener measured in human milk was PCB 153, followed by PCB 138 and PCB 180. The lower chlorinated congeners PCBs (28, 52 and 101) were found below the limit of detection in most individual samples. The median level of the Indicator PCBs in milk samples was 29.1 ng/g lipid weight. The highest PCBs levels were found in breast milk from primiparae mothers 36 - 40 age (36.8 ng/g lipid as a sum of six Indicator PCBs), suggesting bioaccumulation of these pollutants. Conclusions: Positive association was found between the Indicator PCBs levels and the age of mothers. The levels of the Indicator PCBs in breast milk were found to be lower than levels reported in other studies in the European countries.